CHARACTER VALUES FOUND IN ENGLISH TEXTBOOKS OF SENIOR HIGH SCHOOL - Fetriani Fetriani; Indah Hayati (Edu-Ling: Journal of English Education and Linguistics, 2019)
The objective of this research is to find out character values found in English textbook for grade ten and for grade eleven of Senior High School. The research was descriptive qualitative research which dealt with non-numerical data and focused on the character values found in English textbook of senior high school. The result of this research presented the character values found in English textbook for grade ten and for grade eleven of Senior High School. They are religiousness, honesty, tolerance, discipline, perseverance, creativity, independence, democracy, curiosity, nationalism, patriotism, appreciation, friendliness /communication, peacefulness, literacy, affection to nature, sociable, and responsible. From those 18 characters, appreciation character is the most dominant with the percentage of 12.5 %. Meanwhile, tolerance, discipline, independence, democracy, and literacy characters stand in the lowest position with only 2.5 %.